Sustainable Workforce: Peran Employee Engagement pada Perceived Organizational Support terhadap Employee Retention - Sabila, Zetiara Nurul; Gumgum Gumelar; Zarina Akbar (Jurnal Ilmiah Penelitian Psikologi, 2024)
In the competitive realm of the pharmaceutical industry, maintaining a pool of skilled employees stands as a paramount challenge for ensuring company. This study endeavors to explore the interplay between Perceived Organizational Support (POS) and employee retention rates, specifically emphasizing the concept of employee engagement with a quantitative methodology. The study conducted purposive sampling to survey 212 employees from the private pharmaceutical sector in Jabodetabek, each boasting a minimum tenure of 6 months. The instruments study, adapted for this study, encompassed the Employee Retention instrument (Kyndt et al., 2009), Survey of Perceived Organizational Support (Eisenberger et al., 2020), and Employee Engagement Scale (Shuck et al., 2016). The findings unveil a substantial positive influence of POS on employee retention, contributing to a noteworthy 59%. Furthermore, employee engagement emerged as a pivotal mediating factor in the nexus between POS and employee retention rates, constituting a significant 33.8%. The study's outcomes refute the null hypothesis (Ho) and substantiate the alternative hypothesis (Ha), revealing that the impact of perceived organizational support on employee retention is intricately mediated by employee engagement. In conclusion, this study provides valuable insights and references relevant to organizational support and employee engagement strategies, crucial for retaining skilled personnel within the pharmaceutical industry.